The Impact of Doing Assignments with Chatbots on The Students’ Working Memory - Rostami, Mehdi; Mehdi Abadi, Parichehr (Health Nexus, 2023)
This study aimed to investigates the effects of chatbot usage on working memory in students who do their assignments with chatbots. The research employed a Single-Subject AB design involving three participants, with each phase consisting of four measurements. Remarkably, the study revealed diverse outcomes: one participant exhibited no significant change in working memory, another showed a decrease, and the third experienced a gradual increase. These varied results suggest that chatbots can have differential impacts on working memory, potentially explained by cognitive load theory. This theory emphasizes the importance of optimizing technology use in learning environments to support working memory functions. The study's findings indicate that chatbots, as an educational tool, can have complex and varying effects on students' cognitive abilities, particularly in terms of working memory.